2016
DOI: 10.18869/acadpub.johe.5.2.98
|View full text |Cite
|
Sign up to set email alerts
|

The association of anxiety and depression with musculoskeletal disorders among military personnel in 2016

Abstract: Background: Musculoskeletal pain accompanied by psychological problems leads to reduced health efficiency. On the other hand, work-related anxiety and depression is another important factor that could result in reduced productivity in organizations and physical and mental problems in personnel. Musculoskeletal disorders (MSDs) are the most common occupational health problems that have high costs and lead to productivity loss in military personnel. The purpose of this study was to evaluate the association of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…In a study on computer operators, a significant association between job stress and musculoskeletal symptoms in the back was found but no significant association was obtained with MSDs in the neck, shoulders, elbows, hands, and wrists [41]. In a study among military personnel, significant association of anxiety and depression with MSDs was reported [42]. A systematic review integrated strong evidence of an association between knee pain and anxiety, depression, and poor mental health [43], including three randomized clinical trials that showed treatment with antidepressant drug was related to pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…In a study on computer operators, a significant association between job stress and musculoskeletal symptoms in the back was found but no significant association was obtained with MSDs in the neck, shoulders, elbows, hands, and wrists [41]. In a study among military personnel, significant association of anxiety and depression with MSDs was reported [42]. A systematic review integrated strong evidence of an association between knee pain and anxiety, depression, and poor mental health [43], including three randomized clinical trials that showed treatment with antidepressant drug was related to pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…The office workers who had more than one year of work experience and worked with computers for at least 3 hours a day on average (12)(13)(14)16) were enrolled in the study. Individuals with a history of major musculoskeletal trauma and neurological or orthopedic diseases were not included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…In the conducted studies, various areas, such as the neck, lower back, or shoulder, have been mentioned as the most common MSDs in computer users (1,6,(9)(10)(11)(12). The relationship between the ergonomic hazards of different parts of the desk with the MSDs of computer users is not clear.…”
mentioning
confidence: 99%